Chromium accumulation in maize and cowpea after successive applications of composted tannery sludge - Sousa, Ricardo Silva De; Nunes, Luis Alfredo Pinheiro Leal; Lima, Aurenivia Bonifacio De; Melo, Wanderley Jose De; Antunes, Jadson Emanuel Lopes; Araujo, Ademir Sérgio Ferreira De (Editora da Universidade Estadual de Maringá - EDUEM, 2018)
ABSTRACT. Chromium (Cr) accumulation in soil and plants has been reported after successive applications of tannery sludge, which is a matter of concern because Cr can promote environmental contamination and affect the food chain. In this study, we evaluated the growth of and Cr accumulation in maize and cowpea after seven years of consecutive applications of composted tannery sludge (CTS) under field conditions. The experiment consisted of application of CTS at five levels: 0 (control), 2.5, 5, 10, and 20 Mg ha-1 (dry basis). The growth of and Cr accumulation in maize and cowpea were evaluated at 75 and 65 days after plant emergence, respectively. CTS application increased the shoot biomass of maize and cowpea. Accumulation of Cr was similar for both plant species, with higher accumulation in roots. However, Cr accumulation in grains differed as the CTS doses increased; cowpea accumulated more Cr while maize did not accumulate more Cr in grains with higher CTS doses. In conclusion, application of CTS led to higher growth of maize and cowpea plants, and both species exhibited similar Cr accumulation in roots and shoots.

RESUMO. A acumulação de cromo (Cr) no solo e nas plantas tem sido relatada após sucessivas aplicações de lodo de curtume, o que é motivo de preocupação tendo em vista que este elemento pode promover a contaminação ambiental e afetar a cadeia alimentar. Neste estudo, avaliou-se o crescimento e a acumulação de Cr no milho e caupi após sete anos de aplicações consecutivas de lodo de curtume compostado (LCC) em condições de campo. O experimento consistiu na aplicação de LCC em cinco doses: 0 (controle); 2,5; 5; 10 e 20 Mg ha-1 (base seca). O crescimento e o acúmulo de Cr no milho e no caupi foram avaliados aos 75 e 65 dias após a emergência das plantas, respectivamente. A aplicação de LCC aumentou a biomassa do milho e caupi. A acumulação de Cr foi semelhante para ambas as espécies, com maior acumulação relatada nas raízes. No entanto, a acumulação de Cr nos grãos diferiu entre as espécies: o caupi acumulou Cr, enquanto o milho não acumulou esse elemento nos grãos. Em conclusão, a aplicação de LCC proporcionou maior crescimento de plantas de milho e feijão-caupi, e ambas as espécies apresentaram respostas semelhantes à acumulação de Cr nas raízes e parte aérea.
Acumulação de cromo em milho e feijão-caupi após aplicações sucessivas de lodo de curtume compostado
Keywords: waste management; tannery sludge; plant and soil interaction; metals; gestão de resíduos; lodo de curtume; interação planta e solo; metais